2018
DOI: 10.3233/jad-170938
|View full text |Cite
|
Sign up to set email alerts
|

Associations between the Frailty Index and Brain Atrophy: The Treviso Dementia (TREDEM) Registry

Abstract: The FI is associated with the presence, degree, and some localization of cerebral atrophy in a population of cognitive-decline patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 43 publications
2
30
1
Order By: Relevance
“…The results indicate that PD patients had globally decreased gray matter volume, especially in left superior temporal gyrus, right uncus, and left inferior temporal gyrus compared to healthy controls. This is indeed consistent with previous studies reporting that physical frailty and sarcopenia are linked to brain structure changes [22,23], suggesting the role of the central nervous system in the pathophysiology of physical frailty [12]. Partial correlation analysis revealed the gray matter volume reductions in specific regions, such as the uncus and superior temporal gyrus, were significantly associated with fatty infiltration in PD patients.…”
Section: Effects Of Clinical Variables On Core Muscle Fatty Infiltratsupporting
confidence: 91%
See 1 more Smart Citation
“…The results indicate that PD patients had globally decreased gray matter volume, especially in left superior temporal gyrus, right uncus, and left inferior temporal gyrus compared to healthy controls. This is indeed consistent with previous studies reporting that physical frailty and sarcopenia are linked to brain structure changes [22,23], suggesting the role of the central nervous system in the pathophysiology of physical frailty [12]. Partial correlation analysis revealed the gray matter volume reductions in specific regions, such as the uncus and superior temporal gyrus, were significantly associated with fatty infiltration in PD patients.…”
Section: Effects Of Clinical Variables On Core Muscle Fatty Infiltratsupporting
confidence: 91%
“…Volume reductions in several brain regions, such as the uncus and superior temporal gyrus are a risk factor of core muscle loss in PD patients. Although studies have reported that these brain regions are associated with decreased muscle mass, weakness, muscle dysfunction, and sarcopenia [12,22,23], the precise associations between these brain regions, and the mechanisms causing core muscle loss in PD patients, have yet to be elucidated.…”
Section: Possible Effects Of Brain Structural Changes On Core Muscle mentioning
confidence: 99%
“…There are several possible explanations for this result. First, frailty is a condition that is characterized by a reduction in the homeostatic reserves of the individual, which entails an increased vulnerability to endogenous and exogenous stressors [43]. Hence, frail people face more challenges in adapting to significant threats that may occur in that individual's life.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that in a population of cognitively declining patients, frailty is associated with the presence, degree, and localization of cerebral atrophy. For every 1% increase in FI, the probability of cortical atrophy increased by 2% [43]. In a long-term follow-up cohort study, participants may become deceased during the follow-up period, especially those who are frail.…”
Section: Discussionmentioning
confidence: 99%
“…Although the prevalence of cognitive frailty in the community setting is low (1.0–1.8%), it has been associated with a high risk of disability, poor quality of life, and death ( Sugimoto et al, 2018 ). Furthermore, researchers have also found a 50-item frailty index (FI) to be significantly associated with temporal and frontal cortical atrophy, detected by computerized axial tomography, which indicates that frailty and cognitive decline might share common pathophysiological mechanisms ( Fougere et al, 2017 ; Gallucci et al, 2018 ). All of these findings show that frailty and cognitive impairment are closely related to each other.…”
Section: Introductionmentioning
confidence: 99%